Diagnostic performance of ARFI ultrasound elastography in spleen stiffness measurement to predict esophageal varices - Mahesh Seetharam; Rajendra Kumar L. Narasipur; Vinaya M. Gowda; Pradeep N. Hagalahalli; Nanjaraj P. Chakenahalli; Muralidhara P. Chennagiri (Al Ameen Medical College, 2022)
Background: Presence esophageal varices are an independent predictor of mortality in patients with cirrhosis. Non-invasive assessment of cirrhotic patients to predict esophageal varices have been increasingly used instead of endoscopy. The aim of this study is to assess the diagnostic performance of ARFI elastography in measuring spleen stiffness to predict esophageal varices with endoscopy as the gold standard and compare these results with platelet count and spleen size. Methods: The patients included in the study underwent ARFI elastography and underwent endoscopy to determine esophageal varices stage, platelet count and spleen size values were calculated. The diagnostic performance of spleen stiffness by ARFI elastography, platelet count and spleen size was evaluated using receiver operating characteristic (ROC) curve analysis. Correlations of ARFI Elastography, platelet count and spleen size with endoscopy findings (as the reference standard) were determined using Spearman's correlation coefficient. Results: Study included 102 patients of the 58 (56.86%) were grade 0 with mean ARFI elastography value of 20.80±0.92 kPa, 25(26.32%) were grade1 with mean ARFI elastography value of 24.89±2.02kPa, 12(11.76%) were grade 2 with mean ARFI elastography value of 33.50±1.36 kPa, and 07(6.86%) were grade 3 with mean ARFI elastography value of36.37±0.75 kPa. There was significant positive correlation between different stages of esophageal varices by endoscopy and spleen stiffness detected by ARFI elastography (r = 0.995, p < 0.001).ARFI elastography spleen stiffness exhibited higher diagnostic accuracy than the platelet and spleen size for the diagnosis of those without varices AUC 0.991 (0.949 to 1.000), 0.973(0.920 to 0.995), 0.968(0.913 to 0.993) and those with high grade varices AUC 1.000(0.964 to 1.000), 0.995(0.955 to 1.000), 0.901(0.826 to 0.952) respectively. Conclusions: ARFI elastography spleen stiffness measurement is a novel non-invasive method to use in the clinical practice, for the screening esophageal varices in cirrhotic patients, and thus reducing the number of endoscopic examinations burden with high diagnostic performance.